ANALISIS KINERJA USAHA MIKRO KECIL DAN MENENGAH DI KOTA MAKASSAR - Syamsul Alam (Jurnal Bisnis dan Kewirausahaan, 2016)
Access information is positive and significant effect on the Performance of Micro, Small and Medium Enterprises. It can be seen from the value t count > t table (3.240 > 2.020) and a significant value < significance level (α) 0.05 ( 0.002 < 0.05). Marketing communications positive and significant effect on the Performance of Micro, Small and Medium Enterprises. It can be seen from the value t count > t table (5.632 > 2.020) and a significant value < significance level (α) 0.05 ( 0.000 < 0.05) . Access to Information and marketing communications simultaneously positive and significant impact on the performance of Micro, Small and Medium Enterprises. It can be seen from the value of F count> F table ( 34.254 > 3.226 ) and a significant value < significance level (α) 0.05 (0.000 < 0.05) .